Implicit non-linear robust control for an electrohydraulic system with uncertainties - M. R. Quintas (1996)
This paper deals with tracking the position of a linear cylinder moving a mass and controlled by a servovalve. The model of this system is non-linear with respect to state and input and has bounded uncertainties. Uncertainties are considered about the leakage flowrate of the servovalve and about the mass in movement. An implicit non-linear control with a robust term designed by the Corless-Leitmann approach is described step by step. Simulation results are shown in order to point out the advantages of this approach.